RISK MANAGEMENT IN THE HOUSING AND COMMUNAL SERVICES: REGIONAL DIMENSION FOR EXAMPLE REPUBLIC OF DAGHESTAN - A. M. Sherifov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In this article are defined and classified the risks in the housing sector, both at national level and regional. The necessity of establishing an effective mechanism for risk - management utilities in modern conditions of market economy and the uncertainty of the reformation.